Catalyst-Controlled Regio- and Stereoselective Bromolactonization with Chiral Bifunctional Sulfides - Tsuchihashi, Ayano; Shirakawa, Seiji (Synlett, 2019)
Highly regioselective 5-exo bromolactonizations of stilbene-type carboxylic acids bearing electron-withdrawing substituents are achieved for the first time via the use of chiral bifunctional sulfide catalysts possessing a urea moiety. The chiral phthalide products are obtained in moderate to good enantioselectivities as the result of 5-exo cyclizations.
Keywords: asymmetric synthesis; lactonization; organocatalysis; regioselectivity; sulfides